Does Periodontal Treatment Help in Arterial Hypertension Control? A Systematic Review of Literature - Lanau, Neus; Mareque-Bueno, Javier; Zabalza, Michel (European Journal of Dentistry, 2020)
Arterial hypertension and periodontal diseases are two of the pathologies with more prevalence worldwide. In the last few years, several scientific evidences have demonstrated the relationship between both diseases. Besides the etiopathogenic and causal relationship, some recent publications have pointed out that the therapeutic approach of periodontitis could have positive effects on the control of arterial hypertension.The aim of this systematic review is to determine whether there is a decrease in or better control of blood pressure after performing nonsurgical periodontal treatment in patients with periodontitis.A thorough search in PubMed, Scopus, and ISI Web of Science databases with the keywords “‘periodontal disease’ OR ‘periodontitis’ OR ‘periodontal’ AND ‘blood pressure’ OR ‘hypertension’ OR ‘arterial hypertension’” was conducted. The quality of the reported information was assessed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement for systematic reviews.Eight articles were considered for this systematic review. Five of the studies showed statistically significant reduction in systolic blood pressure (SBP) values.Despite the limitations of the review, nonsurgical treatment of periodontal disease seems to reduce SBP values. Further research with larger and longer-term clinical trials are needed to demonstrate this potential positive effect.
Keywords: periodontitis; hypertension; blood pressure; periodontal disease; periodontal therapy